Analisis Komparatif Perlakuan Akuntansi Atas Pendapatan Dan Beban - Apriansyah, Ahmad; Pramiudi, Udi; Setiawan, Hendra (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
This study is aimed at (1) identifying accounting treatment on revenue and cost) at Tas Tajur, (2) identifying accounting treatment on revenue and cost of Tas Tajur in accordance with SAK EMKM, and (3) identifying the comparison of revenue and cost before and after the SAK EMKM. Method of analysis used is descriptive qualitative analysis to describe accounting treatment on revenue and cost of Tas Tajur in accordance with SAK EMKM, and comparing revenue and cost before and after the application of SAK EMKM. Both primary and secondary data are used in this study. The result shows that accounting treatment of revenue and cost at Tas Tajur are based on cash basis. The accounting treatment of revenue and cost in accordance with SAK EMKM using the accrual basis recognized the cost of depreciation and tax cost of the income from the business activities. The accounting treatment already in accordance with SAK EMKM in recognizing the revenue but the assumption used does not match because Tas Tajur uses cash basis, the cost is recognized is in accordance with SAK EMKM but does not recognized the existence of cost of depreciation for the assets owned and does not recognized the existence of tax cost.